SYSTEMIC AND LOCAL IMMUNOGLOBULIN STATUS IN PATIENTS WITH ARTHROSO-ARTHRITIS - Б. Хамдамов; Ф. Хамроєв; У. Набієва; Г. Расулов; А. Хамдамов; С. Давлатов; І. Хамдамов (Неонатологія, хірургія та перинатальна медицина)
Although the development of osteoarthritis (OA) does not affect life expectancy, it is one of the leading causes of premature disability after ischemic heart disease and the most common indication for joint arthroplasty. However, the influence of the state of local immunity on the course and outcome of OA remains unknown.